Occlusion technique in swimming: a training method to improve exchange block time in swimming relays - Conceição, A.; Costa, A. M.; Silva, A. J.; Sobreiro, P.; Louro, H. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Swimming relay events have the concern regarding a good start is shared between the incoming and outgoing swimmers. The aim of this study was to evaluate changes in exchange block time (EBT) for swimming relay events as a result of a four-week training program using the occlusion technique. METHODS: Twenty-eight national swimmers, 12 males (age: 17±1.83 years) and 16 females (age: 19.94±5.65 years) participated in this study. Subjects were required to undergo a training program on visual perception in relay swimming over the course of four weeks; they watched videos corresponding to the last movements of a swimmer during a 4×100m freestyle relay event. The videos were presented with temporal occlusion corresponding to predetermined approaching distances (7.5 m, 5.0 m, and 2.5 m). Swimmers were required to simulate a typical position for exiting the block and to estimate the time-to-contact of the incoming swimmer. The EBT was collected during a real 4×100-m freestyle competition before and after the application of the training program. RESULTS: Female swimmers showed a decreased in EBT, with an improvement of 1.42%, despite there not being a significant difference (P=0.68). The male swimmers had a higher improvement in EBT after the training, with a decrease of 13.34% (P=0.68). CONCLUSIONS: Visual perception practice using video occlusion techniques seems to have a positive effect. On EBT in swimming relay events, particularly in female swimmers.